Effects of rosettes quality and ordering on yield potential in strawberry - Ana Selamovska, K. Nikolic (ISHS Acta Horticulturae, 2009)
The influence of the rosettes quality and ordering depending on planting period upon the yield potential, the yield and the fruit quality of strawberries was determined during the researches. The primary rosettes are of better quality, they have a bigger diameter of the root crown, form bigger yield potential and give a higher yield than secondary rosettes. The biggest differences between researched parameters are found the first year after planting. Significant differences between fruit mass of primary and secondary rosettes are not found. Primary and secondary rosettes that are planted in August form a bigger yield potential; they give a higher yield and form bigger fruits than the ones planted later.
Keywords: rosettes, quality, primary, secondary, planting date, yield